The synthesis of silver nanowires with tunable diameters using halide ions for flexible transparent conductive films. Issue 48 (20th November 2020) - Zhu, Xingzhong; Guo, Aoqi; Xu, Juan; Kan, Caixia
Abstract : The diameter of Ag nanowires could be tuned in the range of 19 to 35 nm with the cooperation of Cl − and Br − ions. Abstract : Ag nanowires (Ag NWs) have attracted great interest as the most promising candidate for the innovation-driven development of flexible transparent conductive films. The use of the halide ions Cl − and Br − is an effective method to reduce the diameter of Ag NWs. However, many research efforts have paid more attention to the role of Br −, neglecting the cooperative relationship between Cl − and Br − ions. Herein, we prepared Ag NWs with a high aspect ratio through tailoring the amounts and ratios of Cl − and Br − ions, together with the use of a syringe pump. The reaction process was monitored, and Cl − and Br − were employed to control the nucleation and elongation of the Ag NWs and to subsequently adjust the concentration of Ag + to slow the reduction kinetics. Additionally, the uniformity and purity of the Ag NWs were dependent on the ratio between Cl − and Br −, with the optimum point being 2 : 1. Ag NWs with tunable diameters from 35 to 19 nm and aspect ratios of up to 1500 were synthesized via adjusting the total concentration of halide ions while keeping their ratio constant. Flexible transparent conductive films based on the purified ultralong Ag NWs exhibit a low sheet resistance of 20 Ω sq −1 and transmittance of 95% at 550 nm after being treated with NaBH4 and spin-coated with polymethyl methacrylate. Furthermore, the obtained composite films could reach a temperature of 51 °C in 30 s at 3 V and return to room temperature at the same rate. Overall, the combination of Cl − and Br − could be used to effectively fabricate Ag NWs with tunable diameter, which have great potential for use in flexible transparent conductive films in the field of film heaters.